Parenting Stress and Coping Capacity Linked with Quality of Life among Parents of Children with Autism Spectrum Disorder (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Autism spectrum disorder (ASD) is prevalent globally. Fundamental impairment of communication and social interactions are common features of ASD children. Parents of autistic children experience parenting differently with severe physical and psychological problems involved and suffer from higher parenting stress which ultimately influence their quality of life. Empowering parents of children with autism for use of available social support, to get assistance of coping strategies and to promote self confidence of odd feelings are essential for enabling the parents to improve their quality of life by reducing theirstress.Objectives: To assess the link of parenting stress and coping capacity with quality of life among the parents whose children suffer from autism spectrum disorder (ASD) and to help the government and relevant organizations take the required steps to improve the living conditions of the parents of children having ASD.Materials and Methods: This cross-sectional study was executed from July 2016 to June 2017 among 175 parents whose children have autism spectrum disorder. Data were collected by in-person interview method with systematic random sampling followed by semi-structured questionnaire.Results: Majority (48.6%) of the parents were between 31 to 40 years of age and mean (±SD) age of the parents was 37.75 ±8.04 with the range of 21-64 years. Most (53.7%) of the parents were female. Majority of the parents (42.9%) were educated up to graduation level and (72.0%) were service holders. Most (93.1%) parents were from urban areas and (92.6%) parents were represents from nuclear family. Majority parents (55.4%) had 2 children and most (70.9%) children have noticed their first symptom at the age of 2 and maximum (47.4%) children were identified with ASD at three years of age. Maximum (62.9%) family had monthly income of Tk. 20001-50000 and majority children (77.1%) were diagnosed in different government hospitals.Conclusion: Considering the fact that ASD is a mushrooming public health problem in Bangladesh, widespread prior diagnostic facilities are needed to be made available all over the country especially in peri-urban and urban areas, to measure the parenting stress and identify ways of coping capacity for improving lives of parents whose children have ASD.Journal of Armed Forces Medical College Bangladesh Vol.15 (1) 2019: 48-54